Rice seed market segments for Ethiopia - Connor, Melanie; Atnaf, Mulugeta; Malabayabas, Arelene; Anbacha, Abiyot; Bazie, Melkamu (CGIAR, 2025)
Rice is a relatively new crop in Ethiopia, but its production is steadily increasing. It has been emphasized by the government as a potential avenue to improve food security because of its suitability under diverse agroecosystems. This brief provides insights into rice seed product market segments currently found in Ethiopia and will provide an evaluation of the current rice market segments and their associated Target Product Profiles (TPPs) to inform rice breeding strategies in Ethiopia. We collected data in 2024 through a partnership with the Ethiopian Institute of Agricultural Research using a standardized assessment tool developed by the International Rice Research Institute. Results show that rice is grown on 178,000 hectares across nine different regions and several ecosystems, with upland being the most prominent (70%), followed by rainfed lowland (28%). The results further indicate that about 50% of the rice cultivation occurs in the high-elevation areas of the country, while the remaining 50% takes place in the low-elevation areas. All rice production in Ethiopia is direct seeded, which needs to be reflected in the current market segmentation and TPPs. Furthermore, stakeholders highlighted medium maturity (115–125 days) as the preferred maturity. The most preferred grain shape is long slender (length:breadth >3.0) with a firm texture. The results further inform important traits to be included in product design: nutrient- and water-use efficiency, weed suppression, grain zinc content, aroma, and diverse biotic stresses.